Antioxidant and Anti-Breast Cancer from Uncaria gambir Roxb Leaves: In Silico & In Vitro Study - Iskandar, Dodi; Rollando, Rollando; Susana, Susana; Amperawati, Suharyani; Indrastuti, Y Erning; Afthoni, Muhammad Hilmi (Majalah Obat Tradisional, 2024)
Uncaria gambir Roxb (URG) is one of the plants from West Kalimantan predicted to contain antioxidant and anti-breast cancer. This study aims to test the antioxidant and anti-breast cancer potential. UGR leaves were extracted by infusion method using water for 15 minutes with 4 repetitions at a temperature 70oC. A thick extract of 96.2351 grams (29.979%) was obtained from a sample weight of 321 grams of dried UGR leaves. In vitro antioxidant assay of the extract was investigated using 2,2-diphenylpicrylhydrazyl (DPPH) with positive control using quercetin and ascorbic acid, and the Ferric Reducing Antioxidant Power (FRAP) method. In silico screening showed that the biological agents in UGR had the potential as TP53 expression enhancer, antioxidant, anticarcinogenic, chemopreventive, and free radical scavenger. The antioxidant bioassay results showed IC50 values of 81.21 μg/mL, 73.39 μg/mL, and 9.17 μg/mL in DPPH for extract samples with positive control quercetin, sample extracts with positive control Vitamin C and Vitamin C with positive control quercetin, respectively. Meanwhile, the antioxidant activity of extract samples with the FRAP method showed value of 66,05 μg/mL. Anticancer bioassay result showed that UGR leaves extract with water solvent had the stron potentgial to inhibit 4T1 cells with IC50  87.72 μg/mL.